Examining the relationship between attitudes toward science and socioeconomic status among middle-class, midwestern middle school students - Porter-Stransky, Kirsten A.; Yang, Wenxin; Vollbrecht, Peter J. (Frontiers in Education, 2024)
Background: Previous research has uncovered disparities in children's attitudes toward science based on gender, income, parenting, geographical location, and school resources, among other factors. However, less is known about socioeconomic influences on science attitudes within the evolving rural middle class. The present study investigated the relationship between indicators of socioeconomic status on middle schoolers' attitudes toward science in a predominantly middle class, white, rural sample within the midwestern United States of America. Methods: Parents were asked for demographic information and consent for their child participating in the study. Middle school children were invited to complete a short survey quantifying their attitudes toward science.Results: Science attitudes did not vary based on gender. However, students with at least one parent that earned at least a bachelor's degree or from a household income exceeding $90,000 had more positive attitudes toward science than those whose parents did not obtain a college degree or whose household income was less than $90,000, respectively. Regression revealed that household income and parent's assessment of their child's interest in a scientific career significantly predicted a child's attitudes toward science, but gender and highest degree earned by a parent did not.Conclusions: This study found differences in children's science attitudes within a rural, predominantly middle-class population. This finding contributes to the literature by revealing differences in science attitudes relating to higher levels of parental education (bachelor's degree) and income ($90,000) than previously identified. This highlights additional opportunities to support children's science growth and promote equitable science opportunities for everyone.